(3GdJYQja hGdCYdGe ajeG CHge aj GdbQGf ef GdCSeGA hGdGYdGes - (3YHO GdQMef Hf YHO Gddg GdNfYej GdSgjdj GdCfOdSj, CHh GdbGSe,J (B581 (3g` s ((3YHO GdeHGQc GdbhUhfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde GOe GdGSeGA hHYO aEfi bUOJ Cf CPcQ ai gPG GdeNJUQ GdhLjR eG JVefg cJGH Gddg GdYRjR ef PcQ ef de jSejg ajg HGSeg s
(3BNQgG (B:s
(3ShQI GdfGS , GdNfGS gh GdTjWGf ceG CNQLg GHf LQjQ JeJ GdeHgeGJ s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3eJaQbGJs